2006
DOI: 10.1002/ca.20298
|View full text |Cite
|
Sign up to set email alerts
|

Deep fascia on the dorsum of the ankle and foot: Extensor retinacula revisited

Abstract: This study revisits the anatomy of the deep fascia over the distal leg, ankle, and dorsum of the foot. The arrangement of the deep fascia in these regions was recorded in 14 lower limbs of adult cadavers using photographs and drawings. The fascial layer from all three sites was subsequently removed in toto, and serial thickness measurements were made along its entire length. In addition, fiber disposition was studied under polarized light, and sections were stained to demonstrate collagen. The arrangement of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 14 publications
1
25
0
1
Order By: Relevance
“…The gluteal fascia departs from the iliac crest and, through the sacrum and the coccygeal bone, runs to the femoral fascia; the latter will then become the tibial fascia, involving the tibia and fibula, finally enclosing the whole foot 69–72. The gluteus maximus is part of the thoracolumbar fascia, and the fascia of the lower limbs is its logical extension 40.…”
Section: Symptoms and Clinical Scenarios: The Anklementioning
confidence: 99%
“…The gluteal fascia departs from the iliac crest and, through the sacrum and the coccygeal bone, runs to the femoral fascia; the latter will then become the tibial fascia, involving the tibia and fibula, finally enclosing the whole foot 69–72. The gluteus maximus is part of the thoracolumbar fascia, and the fascia of the lower limbs is its logical extension 40.…”
Section: Symptoms and Clinical Scenarios: The Anklementioning
confidence: 99%
“…The small triangular fibrocartilaginous ridge can be depicted as a low-signal-intensity meniscus-like structure close to its origin on the tip of the lateral malleolus. 37 Traumatic injury to the superior peroneal retinaculum is well documented. This lesion is produced by sudden dorsiflexion of the foot.…”
Section: Superior Peroneal Retinaculummentioning
confidence: 99%
“…Probably the role of the IER on this location is limiting side-to-side movement of the EDL rather than preventing bowstringing. Abu-Hijleh et al 1 confirmed that robust loops of the IER exist for the common tendon of the EDL and for the tendon of the EHL but not for the tibialis anterior based on 14 lower limbs of cadavers. The IER was represented by a central thick nodelike (knot) overlying the EDL immediately before it divided into its digital components in their study.…”
Section: Foot and Ankle International/vol 33 No 4/april 2012mentioning
confidence: 96%